2024
DOI: 10.3389/fpsyt.2024.1381124
|View full text |Cite
|
Sign up to set email alerts
|

Is there evidence for factorial invariance of the COVID Stress Scales? an analysis of North American and cross-cultural populations

Blake A. E. Boehme,
Laura Kinsman,
Steven Taylor
et al.

Abstract: The COVID-19 pandemic impacted the mental health of more citizens globally than any previous modern viral outbreak. In response to the psychological challenges associated with COVID-19, the COVID Stress Scales (CSS) were developed to assess the presence and severity of COVID-related distress. The initial North American validation study of the CSS identified that the scale comprised five factors: danger and contamination fears, fear of socioeconomic consequences, xenophobia, checking and reassurance seeking, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Using latent class analysis, they found that a substantial percentage of the sample fell in the most severe class of COVID stress syndrome severity; CSS scores were also associated with pre-existing mental health concerns and coping difficulties during the pandemic. Recent research also provides evidence of factorial invariance of the CSS across various demographic variables (Boehme et al, 2024). McKay and Asmundson (2020) suggested that facets of the COVID stress syndrome may readily perpetuate substance misuse as a maladaptive coping mechanism for pandemicrelated distress.…”
Section: Profile Analysis Of Covid Stress Scalesmentioning
confidence: 99%
“…Using latent class analysis, they found that a substantial percentage of the sample fell in the most severe class of COVID stress syndrome severity; CSS scores were also associated with pre-existing mental health concerns and coping difficulties during the pandemic. Recent research also provides evidence of factorial invariance of the CSS across various demographic variables (Boehme et al, 2024). McKay and Asmundson (2020) suggested that facets of the COVID stress syndrome may readily perpetuate substance misuse as a maladaptive coping mechanism for pandemicrelated distress.…”
Section: Profile Analysis Of Covid Stress Scalesmentioning
confidence: 99%